Patient Preferences for Benefit and Risk Associated With High Intensity Focused Ultrasound for the Ablation of Prostate Tissue in Men With Localized Prostate Cancer - Babalola, Olufemi; Gebben, David; Tarver, Michelle E.; (Joyce) Lee, Ting-Hsuan; Wang, Shu; Siddiqui, M. Minhaj; Sonn, Geoffrey A.; Viviano, Charles J. (Clinical genitourinary cancer, 2024)
•When considering high intensity focused ultrasound (HIFU) ablation therapies, patients marginally prioritized urinary incontinence (UI) over prostate biopsy outcomes, and erectile dysfunction (ED) was the least important outcome.•Patients are willing to accept increased risk of ED or UI to obtain an increased chance of favorable biopsy outcome.•Results from this study may help inform development and evaluation of future HIFU ablation therapies. Food and Drug Administration must make decisions about emerging high intensity focused ultrasound (HIFU) devices that may lack relevant clinical oncologic data but present with known side effects. This study aims to capture patients’ perspective by quantifying their preferences regarding the available benefit and important side effects associated with HIFU for localized prostate cancer. Preferences for HIFU outcomes were examined using a discrete choice experiment survey. Participants were asked to choose a preferred treatment option in 9 choice questions. Each included a pair of hypothetical treatment profiles that have similar attributes/outcomes with varying levels. Outcomes included prostate biopsy outcome and treatment-related risks of erectile dysfunction (ED) and urinary incontinence (UI). We calculated the maximum risk of side effect patients were willing to tolerate in exchange for increased benefit. Preferences were further explored via clinical and demographic data. About 223 subjects with a mean age of 64.8 years completed the survey. Respondents were willing to accept a 1.51%-point increase in new ED risk for a 1%-point increase in favorable biopsy outcome. They were also willing to accept a 0.93%-point increase in new UI risk for a 1%-point increase in biopsy outcome. Subjects who perceived their cancer to be more aggressive had higher risk tolerance for UI. Younger men were willing to tolerate less ED risk than older men. Respondents with greater than college level of education had a lower risk tolerance for ED or UI. Results may inform development and regulatory evaluation for future HIFU ablation devices by providing supplemental information from the patient perspective. Emerging high intensity focused ultrasound devices may lack relevant clinical oncologic data but present with known side effects. A discrete choice experiment showed that patients with localized prostate cancer were willing to accept increased treatment-related risk of erectile dysfunction or urinary incontinence to obtain increased chance of favorable biopsy outcome. Results may inform development and evaluation of future HIFU therapies.